Синтез N-кумінпохідних імідів дикарбонових кислот С4 - Якимович, А. Б.; Долинська, Л. В.; Гевусь, О. І.; Yakymovych, A. B.; Dolynska, L. V.; Hevus, O. I. (Lviv Politechnic Publishing House, 2018)
Синтезовано похідні імідів малеїнової та бурштинової кислот – N-(4-ізопро- пілбензил)сукцинімід та N-(4-ізопропілбензил)малеімід. Сполуки отримано взаємодією вихідних імідівдикарбонових кислот та п-хлорметилкумену у середовищі диметилфор- маміду за участю карбонату калію. Досліджено реакційну здатність вихідних імідів з п- хлорметилкуменом. Отримані сполуки можуть бути використані як напівпродукти для синтезу передавачів ланцюга у реакціях радикальної полімеризації. Будову отриманих сполук підтверджено фізико-хімічними методами, елементним та функціональним аналізом.

The imides of maleic and succinic acids derivatives such as N-(4-isopropylbenzyl) succinimideта N-(4-isopropylbenzyl)maleimidewere synthesized. The compounds were obtained by interaction of imides dicaboxylic acids and p-chloromethylcumeneasstartingmaterialswithpotassiumcarbonateastheonlycoreagent in dimethylformamide media. Reactivity of imides with p-chloromethylcumene was investigated. The obtained compounds can be used as intermediates for synthesis of transmitters of the polymerization chain. Thestructureof the of obtained compounds is confirmed by physical and chemical methods, elemental and functional analysis.
Synthesis of N-isopropylbenzyl derivatives of imides of dicarboxylic acids C4
Keywords: ізопропілбензилсукцинімід; ізопропілбензилмалеімід; п-хлорметил-кумен; синтез; алкілювання; isopropylbenzylsuccinimide; isopropylbenzylmaleimide; p-chloromethylcumene; synthesis; alkylation